Transcriptome analysis of the compatible interaction of tomato with Verticillium dahliae using RNA-sequencing - Tan, Guangxuan; Liu, Kun; Kang, Jingmin; Xu, Kedong; Zhang, Yi; Hu, Lizong; Zhang, Ju; Li, Chengwei (Frontiers in Plant Science, 2015)
Tomato Verticillium wilt is a soil-borne vascular disease caused by the necrotrophic fungus Verticillium dahliae. Although some understanding of plant defense mechanisms against V. dahliae infection has been gained for incompatible interactions, including identification of inducible resistant genes and defense signaling pathways, the genes and signaling pathways involved in the compatible interaction remain unclear. To investigate the molecular basis of the compatible interaction between tomato and V. dahliae, transcriptomes of V. dahliae infected tomatoes were compared to those of a control group. A total of approximately 25 million high-quality reads were generated by means of the RNA sequencing (RNA-seq) method. The sequence reads were aligned to the tomato reference genome and analyzed to measure gene expression levels, and to identify alternative splicing events. Comparative analysis between the two samples revealed 1,953 significantly differentially expressed genes (DEGs), including 1,281 up-regulated and 672 down-regulated genes. The RNA-Seq output was confirmed using RT-qPCR for ten selected genes. The Nr, Swiss-Prot, GO, COG and KEGG databases were used to annotate DEG functions. Of the 1,953 DEGs identified, 1,953, 1,579, 1,739, 862, and 380 were assigned by Nr, Swiss-Prot, GO, COG, and KEGG, respectively. The important functional groups identified via GO and COG enrichment were those responsible for fundamental biological regulation, secondary metabolism, and signal transduction. Of DEGs assigned to 87 KEGG pathways, most were associated with phenylpropanoid metabolism and plant-pathogen interaction pathways. Most of the DEGs involved in these two pathways were up-regulated, and may be involved in regulating the tomato-V. dahliae compatible interaction. The results will help to identify key susceptible genes and contribute to a better understanding of the mechanisms of tomato susceptible response to V. dahliae.